Merry Christmas, Stinky Face - McCourt, Lisa.; Moore, Cyd (New York : Scholastic, 2004)
On Christmas Eve, a little boy is beset with worries about what could go wrong on Santa's trip, but his mother reassures him with very imaginative solutions.
"Cartwheel books."
4.8
K-3
Keywords: Christmas -- Fiction; Mother and child -- Fiction; Questions and answers -- Fiction; Christmas -- Fiction; Mother-child relationship -- Fiction; Questions and answers -- Fiction